Surgeon Positioning During Awake Laryngeal Surgery: An Ergonomic Analysis. (23rd July 2021) - Baird, Brandon J.; Tynan, Monica A.; Tracy, Lauren F.; Heaton, James T.; Burns, James A.
Abstract : Objectives: While it is acknowledged that otolaryngologists performing microlaryngeal surgery can develop musculoskeletal symptoms due to suboptimal body positioning relative to the patient, flexible laryngoscopy and awake laryngeal surgeries (ALSs) can also pose ergonomic risk. This prospective study measured the effects of posture during ergonomically good and bad positions during laryngoscopy using ergonomic analysis, skin‐surface electromyography (EMG), and self‐reported pain ratings. Study Design: Prospective cohort study. Methods: Eight participants trained in laryngoscopy assumed four ergonomically distinct standing positions (side/near, side/far, front/near, front/far) at three different heights (neutral—top of patient's head in line with examiner's shoulder, high—6 inches above neutral, and low—6 inches below neutral) in relation to a simulated patient. Participants' postures were analyzed using the validated Rapid Upper Limb Assessment (RULA, 1 [best] to 7 [worst]) tool for the 12 positions. Participants then simulated ALS for 10 minutes in a bad position (low‐side‐far) and a good position (neutral‐front‐near) with 12 EMG sensors positioned on the limbs and torso. Results: The position with the worst RULA score was the side/near/high (7.0), and the best was the front/near/neutral (4.5). EMG measurements revealed significant differences between simulated surgery in the bad and good positions, with bad position eliciting an average of 206% greater EMG root‐mean‐squared magnitude across all sampled muscles compared to the good posture (paired t ‐test, df = 7, P < .01), consistent with self‐reported fatigue/pain when positioned poorly. Conclusion: Quantitative and qualitative measurements demonstrate the impact of surgeon posture during simulated laryngoscopy and suggest ergonomically beneficial posture that should facilitate ALSs. Level of Evidence: 3 Laryngoscope, 131:2752–2758, 2021